Equação do primeiro grau
10-2(x+3)=8+3(2x+5)
Soluções para a tarefa
Respondido por
1
Resposta:
-19/8 = x
Explicação:
10-2×(x+3) = 8+3×(2x+5)
10-2x-6 = 8+6x+15
10-6-8-15 = 6x+2x
4-8-15 = 6x+2x
-4-15 = 6x+2x
-19 = 8x
-19/8 = x
Respondido por
1
Resposta: x = -
Explicação passo a passo:
⇔ 10 -2(x+3) = 8 +3(2x+5)
⇔ 10 - 2x -6 = 8 +6x + 15
⇔ - 2x -6x = 8 + 15 -10 +6
⇔ -8x = 19
⇔ x = -
Perguntas interessantes
Psicologia,
7 meses atrás
Matemática,
7 meses atrás
Ed. Física,
7 meses atrás
História,
7 meses atrás
Matemática,
7 meses atrás
Matemática,
1 ano atrás